From the Guest Editor - David Logan (Mathematical Biosciences and Engineering)
This Special Issue of Mathematical Biosciences and Engineering (MBE)contains a few of the papers presented at a special session in Mathematical Biologyat the Regional Meeting of the American Mathematical Society, held in Lincoln, Nebraska,on October 21-23, 2005. The AMS meeting was preceded by a 2-day workshop on educationalissues in mathematical biology, organized by Glenn Ledder. Many of the visitors attendedboth meetings, and therefore the five-day period was an enriching, double-barreled,math biology experience for nearly everyone. Near the end of the session the Editor-in-Chiefof MBE, Yang Kuang, asked if we would be willing to collect together some of the papersfrom the special session for an issue of MBE. For more information please click the “Full Text” button above.